2009
DOI: 10.1002/ijc.24382
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of siRNA specific to tumor mediated by atelocollagen: Combined therapy using siRNA targeting Bcl‐xL and cisplatin against prostate cancer

Abstract: The largest obstacle to the effective use of short interfering RNA (siRNA) in an animal body is the ability to deliver it to the target tissue. Here we showed a systemic delivery method of siRNA specific to pregrown solid tumors via atelocollagen. Atelocollagen facilitated the selective uptake of siRNA into the tumors when an siRNA/atelocollagen complex was administered intravenously to mice. We chose a Bcl‐xL protein as a model target to prove the therapeutic efficacy of the atelocollagen‐mediated method. Bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 44 publications
1
59
0
Order By: Relevance
“…First, synthetic miRNA instead of the plasmid vector should be examined; second, a systemic delivery system of synthetic miRNA specific to tumors should be developed. Toward these ends we have acquired promising results, because we already have much knowledge about how to systemically deliver synthetic small RNA molecules, that is, siRNA, specifically to tumors (22). The systemic therapeutic effect by the synthetic double-stranded RNA mimicking miR-516a-3p complexed with atelocollagen will be described elsewhere in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, synthetic miRNA instead of the plasmid vector should be examined; second, a systemic delivery system of synthetic miRNA specific to tumors should be developed. Toward these ends we have acquired promising results, because we already have much knowledge about how to systemically deliver synthetic small RNA molecules, that is, siRNA, specifically to tumors (22). The systemic therapeutic effect by the synthetic double-stranded RNA mimicking miR-516a-3p complexed with atelocollagen will be described elsewhere in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…On the next day, the cells were washed once with serum-free RPMI 1640. Cell proliferation was monitored with a cell counting kit (Dojin) as reported previously (22). Migration and invasion analysis was performed with BD BioCoat Angiogenesis System-Endothelial Cell Migration and BD BioCoat Fluoroblok Tumor Invasion System (BD Biosciences) according to the manufacturer's instructions.…”
Section: Proliferation Migration and Invasion Analysis In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…8a). A biomaterial, atelocollagen (Koken) acts to deliver synthetic miRNA molecules specific to the 58As9 orthotopic tumors via intravenous injections, as we or the other group reported previously in the case of siRNA/miRNA delivery [21, 22, 36]. On day 20 (at the end point of the therapy), all of the mice were sacrificed, and the primary tumor tissues were excised.…”
Section: Resultsmentioning
confidence: 99%
“…Although these particles have not been modified to target tumors, passive targeting due to the enhanced permeability and retention effect, causes the selective accumulation within the cancerous tissues as shown in several studies with tumor xenografts. 23,[37][38][39] Initial studies indicated that atelocollagen particles could be administered safely without induction of cytokines or observed toxicity to the tissues.…”
Section: Introductionmentioning
confidence: 99%